Hyperekplexia; Response to Clonazepam - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
Sixteen patients, including 1 neonate, in a large 5 generation family with hyperekplexia (startle disease or congenital stiff-man syndrome) were treated with clonazepam at the University of Texas Health Science Center, San Antonio, TX.